2017
DOI: 10.20355/c5s01t
|View full text |Cite
|
Sign up to set email alerts
|

“They Wanted to Study Us; They Didn’t Want to Help Us”: Socially Just and Participatory Research Methodologies for Demographically Changing Schools

Abstract: Educators and leaders across Canada must re-conceptualize their pedagogies and leadership approaches and reflect on their own worldviews to enhance the transitions of new immigrant, international and refugee students into their schools. This paper reports on ongoing case study research in New Brunswick, Canada. The researchers are investigating the impact and implications of immigration and demographic changes on school and community stakeholders. The authors discuss the social justice and participatory method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…We posit that more work is needed in this area of scholarship in New Brunswick, particularly in rural communities where employment opportunities are increasingly abundant for new Canadians. This emerging reality in our province is primarily related to the food-processing and long-haul trucking industries (Hamm, et al, 2017) and is similar to what scholars found in Alberta (Broadway, 2013;Hamm, 2009). As such, "If teachers do not take professional and pedagogical action in their lives as students from diverse backgrounds increasingly enter their classrooms, those students will not be served equitably by their school system" (Hamm, 2009, p. 73).…”
Section: Immigration and The New Brunswick School Systemsupporting
confidence: 79%
See 2 more Smart Citations
“…We posit that more work is needed in this area of scholarship in New Brunswick, particularly in rural communities where employment opportunities are increasingly abundant for new Canadians. This emerging reality in our province is primarily related to the food-processing and long-haul trucking industries (Hamm, et al, 2017) and is similar to what scholars found in Alberta (Broadway, 2013;Hamm, 2009). As such, "If teachers do not take professional and pedagogical action in their lives as students from diverse backgrounds increasingly enter their classrooms, those students will not be served equitably by their school system" (Hamm, 2009, p. 73).…”
Section: Immigration and The New Brunswick School Systemsupporting
confidence: 79%
“…Secondly, what are some effective responses that educators are providing for new Canadian students and their families, during and after their settlement and adjustment in New Brunswick? In our previous studies of New Brunswick, we found that educators experience various levels of stress and anxiety as they help new Canadian students adjust to their new schools and communities (Hamm, 2017;Hamm, Massfeller, Scott, & Cormier, 2017;Massfeller & Hamm, 2019). Still, the academic literature is limited on studies of immigration, demographic change, and diversity in New Brunswick.…”
Section: Immigration and The New Brunswick School Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The voices of rurally situated educators are not well understood by policymakers (Hamm et al, 2017). Many educators experience doubt and anxiety when responding to rapid changes in their schools and communities brought on by demographic shifts.…”
Section: Rurality and Resistance Toward Newcomersmentioning
confidence: 99%